Bacteriological and histological examinations of endometrium from cows showing symptom free sterility - ΣΕΪΤΑΡΙΔΗΣ Κ.; ΤΣΑΓΓΑΡΗΣ Θ.; ΗΛΙΑΔΗΣ Ν.; ΖΩΓΡΑΦΟΠΟΥΛΟΣ Θ.; ΠΑΠΑΔΟΠΟΥΛΟΣ XP. (Journal of the Hellenic Veterinary Medical Society, 2019)
45 uteri from cous were examined bacteriologically and histologically. These cous were slaughtered because of infertility 383 days after they bore for the last time. All the cows 3 - 7 years ofd and oi good or very good nutritional condition were submitted to 9.45 ± 2.08 unsuccessful artificial and natural insemination and did not show in the rectal examination any pathological symptons of the genital system (symptom free sterility). 8 out of these 45 cows that is 17.8% did show pathogen germs and 17 cows that is 37,7% had shown endometritis by histological examination.